ECONOMIC AND TRADE DYNAMICS: ANALYZING THE INTERRELATIONSHIP BETWEEN LOCAL ECONOMY, EXPORTS, AND GLOBAL CPO PRICES - Rineliana, Rineliana; Ridarmin, Ridarmin; Susanto, Edi; Sari, Nana; Tampubolon, Omar Farrakhan; Gunawan, Agung (Jurnal Daya Saing, 2025)
The palm oil industry is a pivotal sector in Indonesia's economy, particularly in Riau Province, significantly contributing to exports and the regional economy. This study aims to analyze the impact of CPO price fluctuations on the regional economy, specifically focusing on the export and investment sectors in Riau Province. Employing a quantitative approach and multiple linear regression analysis, this research examines the relationship between regional economic variables, exports, investments, and world CPO prices throughout 2008-2022. The findings indicate that exports and investments significantly influence world CPO prices, while the regional economy does not directly impact them. This study offers crucial implications for regional economic policies, highlighting the need to strengthen export and investment sectors and implement sustainability policies within the palm oil industry. These findings will serve as a reference for formulating policies that can reduce dependence on global price fluctuations and bolster the local economy.